Providing reliable data?: Combining scientific and historical perspectives on flooding events in late medieval and early modern Nuremberg (1400-1800) - Kluge, Tobias; Schuh, Maximilian (Making the medieval relevant, 2020)
Extreme weather events or climate phases and their consequences were a common threat to premodern societies. Detailed analysis of specific periods and societies requires profound knowledge of the political, economic, social, and climatic background.